FATWA DSN-MUI NO. 108 DSN-MUI (X) 2016TENTANG PEDOMAN PENYELENGGARAAN WISATA BERDASARKAN PRINSIP SYARIAH SEBAGAI FONDASI PENGEMBANGAN WISATA SYARIAH PULAU SANTEN KABUPATEN BANYUWANGI - Ansari; Hali Makki (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2020)
Fatwa DSN-MUI No 108 DSN-MUI (X) 2016 on the guidelines of tourism implementation based on the Sharia principle (P2BPPS). As a cornerstone of coastal tourism development is done with various strategies, one of them with promotion through print media, communication media, advertising media, and other strategies. The strategy and contemplation of tourism development of Santen Island Syariah use SWOT analysis as a strategy of Islamic law as the foundation of Islamic tourism development. Tourism development of Syariah Santen Island is a must in the effort to preserve the socio-cultural peculiarities of Banyuwangi and maintain survival as a tourist destination that can ultimately make a real contribution to creating peace and welfare of the community. To realize this, it takes commitment and cooperation among tourism stakeholders in Banyuwangi as well as the political will from the central and local governments to develop tourism beach Sharia Island Santen Banyuwagi. The study uses qualitative methods of descriptive research with data collection on observations, interviews, and documentation, so this research can be made with the next researcher's reference. From the results of the study found the foundation of tourism development of Sharia Santen Kabupaten Banyuwangi Island, which has been following the fatwa of the National Council of Syariah, the Indonesian Ulama Council in its implementation using Sharia principles.